Effects of laptop screen height on neck and shoulder muscle fatigue and spine loading for office workers. - Guo, Zenghui; Chen, Zhiyuan; Pai, Junjun; Fang, Bin; Liang, Wenhao; Su, Guosheng; Zheng, Feng (Work, 2024)
BACKGROUND: Due to the unfavourable neck-shoulder muscle loads caused by poor posture, the people who use the laptop for a long time may face the risk of neck and shoulder injuries. OBJECTIVE: The purpose of this study investigates the impact of the screen height on the muscle activation of head flexion, neck and shoulder, and the cervical spine torque to provide the favorite screen height for laptop user. METHODS: Twelve healthy young participants completed a 15-minute task of the reading at the four different screen heights. sEMG signals of the splenius capitis (SC) and upper trapezius (UT) were measured and calculated the root mean square (RMS) and mean power frequency (MPF) to determine muscle fatigue. The different height of laptop users was simulated and the forces on the spine of users at different screen heights were analyzed by Jack. RESULTS: Adjusting the height of the laptop screen can effectively reduce head flexion and muscle activity of SC and UT, and has a positive effect on reducing fatigue of SC, but has no significant effect on UT. CONCLUSIONS: Adjusting the height of the laptop screen can delay the occurrence of SC muscle fatigue to a certain extent. The joint analysis of sEMG spectrum and amplitude reports that the screen heights of D15 and D45 have the highest and the lowest frequency of fatigue, respectively. At the same time, the moment of spineT1/T2 and spineL4/L5 decrease with the increase of screen height.